Description of the first extinct member of the tribe Anaglyptini (Coleoptera: Cerambycidae) from European Tertiary - Alekseev, Vitalii Igorevich; Vitali, Francesco (Zootaxa, 2020)
New longhorn beetle taxon, Acanthoglyptus picollus gen. et sp. nov., is described and figured from Baltic amber found in the Baltic Sea coast, Yantarny settlement, Kaliningrad Region, Russia. The new amber inclusions presented here prove the occurrence of the tribe Anaglyptini in the ‘Baltic amber forest’, giving this group at least a Palaeogene age. The closest living relative of the extinct beetle appears to be the Chinese genus Yoshiakioclytus Niisato, 2007. A brief updated list of the described longhorn beetles from European ambers, including 6 subfamilies, 17 tribes, 25 genera, and 27 species is compiled.